1992
DOI: 10.1128/mcb.12.12.5768
|View full text |Cite
|
Sign up to set email alerts
|

P25 gene regulation in Bombyx mori silk gland: two promoter-binding factors have distinct tissue and developmental specificities.

Abstract: The gene encoding the silk protein P25 is expressed in the posterior silk gland of Bombyx mori with strict territorial and developmental specificities. The cis-acting regulatory elements previously located within the 441-bp 5' proximal sequence of the gene were examined for protein-binding capacities. We identified two factors, BMFA and SGFB, that lead to prominent band shifts and the target sites for which are included in a region homologous to the fibroin gene enhancer sequence. Analysis of the tissue-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…This correlates with the footprint on the target DNA in PSG chromatin, strongly suggesting that the factor SGFB, a silk gland-specific protein, acts as a transactivator. In vitro characterization by gel retardation assay, proteolytic clipping, and SGFB-DNA cross-linking did not reveal structural differences between the SGFBs in PSG and MSG cells (5). However, our results clearly show that the silk gland factor stably binds to its target sequence in P25-active cells and not in inactive MSG cells.…”
Section: Discussionmentioning
confidence: 35%
See 2 more Smart Citations
“…This correlates with the footprint on the target DNA in PSG chromatin, strongly suggesting that the factor SGFB, a silk gland-specific protein, acts as a transactivator. In vitro characterization by gel retardation assay, proteolytic clipping, and SGFB-DNA cross-linking did not reveal structural differences between the SGFBs in PSG and MSG cells (5). However, our results clearly show that the silk gland factor stably binds to its target sequence in P25-active cells and not in inactive MSG cells.…”
Section: Discussionmentioning
confidence: 35%
“…The mutations in the Ub2a, Ub2b, BMFA, and SGFB elements which abolish the binding of their cognate factors (5,24) were created by ligating appropriate fragments resulting from 5Ј and 3Ј BAL 31 digestions of P25 DNA. The wild-type sequences were replaced by the same exact number of nucleotides taken from the plasmid polylinker DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated that Bmdimm interacted with Bmsage in nuclei. It has been found that an SGF1-forkhead complex acts as a crucial transcription activator that binds to proximal upstream elements of both the fibroin and p25 genes in PSG cells (55). Our previous study demonstrated that Bmsage is involved in regulation of the fib-H gene via interaction with SGF1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…This sequence interacts with a GATA-like factor in conjunction with the activation of late chorion gene expression in B. mori follicle cells (44,45). An example of temporal and tissue region specificity is provided by work on the expression of the P25 gene in the PSG of B. mori (46,73). This tissue region has approximately 500 cells, and expression of the P25 gene is restricted to PSG at a specific time in development.…”
Section: Temporal Control Cell Type and Tissue-specific Regulatory mentioning
confidence: 99%